Characterization of wood-based multi-material systems under dynamic impact stress. Issue 3 (3rd May 2020) - Kohl, Daniel; von Boyneburgk, C.; Feldmann, M.; Heim, H.-P.; Böhm, S.
ABSTRACT: Due to its naturally grown properties, wood has played a rather subordinate role as a material for technical applications up to now. In this paper, multi-material systems based on veneers of beech ( Fagus sylvatica ) with different reinforcing variants were investigated. In addition to the influence of different adhesive systems (urea formaldehyde and polyurethane), the effect of reinforcing by aramid fiber fabric and stainless steel foil in different climates was examined. At the center of the investigations were dynamically sudden loads, in the form of impact bending and dart drop tests (penetration and impact mode). It has been shown that the use of the reinforcing materials leads to a significant improvement in material properties. The penetration energy of the composites reinforced with the aramid fiber fabric could be increased by 43%. The maximum force in the dart drop test (impact mode) could be increased by 29% with the stainless steel foil, the damping decreased by 48%. The aramid fiber reinforcement achieved an increase in impact resistance by 27% in impact bending test, the steel reinforced achieved an increase of 39%. A clear dependency on both, the climate and the adhesive within the composite, could be demonstrated.